Identifikasi Risiko Ergonomi Dengan Metode Nordic Body Map Terhadap Operator Final Inspection Di PT. JKLM - Rendi Krismanto; Ade Nurul Hidayat (DPPM Universitas Pelita Bangsa, 2022)
JKLM is a manufacturing company engaged in the automotive industry. This company produces several automotive components from Japan. The higher market demand demands the conditions of operator safety and health who must always be healthy and fit to achieve maximum production results. Humans as labour resources have a very influential and significant role in carrying out the production process. Referring to this problem, an analysis was carried out on 2 final inspection operators using the Nordic body map, which is the questionnaire that is most often used to find out discomfort or pain in the body and can identify Work Related Musculoskeletal Disorders (WMSDs) from workers. The first thing to do in this research is to conduct a preliminary analysis, identify ergonomic risks experienced by final inspection operators and provide questionnaires to 2 operator respondents, namely the Nordic body map questionnaire. After the questionnaire was converted to a likert scale, the operator scores 1 (60 points) and operator 2 (51 points) which means that on that scale the level of risk that will occur is in the moderate category according to literature sources, which means that corrective action to the problem may be taken. Action at a later date. Furthermore, to add further cause analysis, the researcher added an interview to the operator and it was found that the body was influenced by non-ergonomic work area settings so that the worker's body positions in activities felt limited, causing problems in the body such as the worker's body often bending over resulting in back pain of workers. Keywords: Ergonomics, Safety, K3, Nordic Body Map, WMSDs